Multimodal switching of a redox-active macrocycle - Daniel T. Payne (Nature Portfolio, 2019)
Molecules that can switch between multiple stable states in response to stimuli are promising for many applications, but are challenging to construct. Here, the authors design a resorcinarene switching manifold with multiple oxidation states and coupled charge-transfer states, which can access up to five distinct switch-states with unique optical outputs.